KEEFEKTIFAN MEDIA WORD WALL UNTUK MENINGKATKAN KEMAMPUAN KOSAKATA BAHASA JEPANG SISWA KELAS 2 SMK SULTHAN MUAZZAM SYAH PEKANBARU - Oktri Mardiyanti; Hadriana Hadriana; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: this research was about the effectively of using word wall media as increasing the Japanese vocabulary of SMK Sulthan Muazzam Syah Pekanbaru of Class 2. This research conducted of to know the effectiveness using word wall media as increasing the Japanese vocabulary in that school. The samples consisted of 2 classes as experiment and control class. The instrument of the research was using pretest and posttest, then given a treatment in experimental class that using word wall media and compared the result as it is. Data analyze technique by using independent samples t-test. The result of the research was by using word wall media can increased the Japanese vocabulary. As it knows, the means was 75,83. The significance in this research was 0,000 < 0,05. So, there was an effect of using word wall media to increase student Japanese vocabulary in SMK Sulthan Muazzam Syah Pekanbaru.Key Words: Vocabulary Learning, Word Wall Media